Chemical composition and potential commercial values of rambutan (Nephelium lappaceum) peel: A review / Syazwani Najwa Zulkurnain and Nurul Azlin Tokiman - Zulkurnain, Syazwani Najwa; Tokiman, Nurul Azlin (2021)
Rambutan (Nephelium lappaceum) peel will be discarded upon processing or consumption but due high antioxidant content, it could attract the interest of experts in related fields. This study summarised the findings on the colouring compound, antioxidant and antimicrobial properties of rambutan peel, as well as the applications of rambutan peel in both food and non-food industries. It showed that flavonoid and anthocyanin are among the natural colouring compounds found in rambutan peel but due to instability on the fabrics, mordant was used for this purpose. On the other hand, a high amount of phenolic content has proved that rambutan peel is high in antioxidants and geranin was reported to be the highest contributor. Antioxidant extraction using methanol reported the highest yield, 67.57% followed by ethanol and water. While phenolic content was employed to determine the antioxidant capacity, ABTS, FRAP, and DPPH assays were used to measure the antioxidant properties of the rambutan peel extract. In addition, the rambutan peel extract also possesses the antimicrobial properties towards gram-positive bacteria such as Staphylococcus aureus. The objective of this paper is to discuss the research findings on the chemical composition and potential commercial values of rambutan (Nephelium lappaceum) peel.